Optimalisasi Peran Guru Sebagai Pengajar dan Pelaku Bisnis syariah pada Tawee Wittaya Islam School Thailand - Ibnu Adani; Isra Hayati (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
This study aims to analyze the optimization of teachers’ roles as educators and sharia business practitioners at Tawee Wittaya Islam School. The study is motivated by the development of the teacherpreneurship concept in Islamic education, which positions teachers not only as educators but also as individuals with sharia-based entrepreneurial abilities. This research employed a qualitative approach with a field research design. Data were collected through semi-structured interviews, observations, and documentation. Data analysis used the Miles, Huberman, and Saldaña interactive model, including data condensation, data display, and conclusion drawing. The findings reveal that the optimization of teachers’ roles is influenced by time management skills, understanding of Islamic business ethics, and institutional support from the school. The major challenges faced by teachers include balancing teaching responsibilities and business activities, limited sharia entrepreneurship skills, and the absence of school regulations regarding teachers’ business practices. The study also shows that the values of siddiq and amanah are important foundations in maintaining teachers’ professionalism. School support through training, ethical guidelines, and the strengthening of Islamic entrepreneurial culture contributes to the sustainable optimization of teachers’ roles